Retention of contract staff among civil servants: statutory bodies agency in Bangi, Malaysia - Abdul Rahman, Mohd Nizam; Arshad, Mohd Mursyid; Md Rami, Ahmad Aizuddin; Ismail, Normala (Human Resource Management Academic Research Society, 2022)
Employee retention is an important issue that requires full focus by an organization as it is a key element that has been identified as the driving force in determining the success and effectiveness of an organization. The concept of employee retention is actually to attract experienced and efficient employees to stay long in service. Among the impulses and reasons for the retention of these employees is to go through a motivational approach or the basis of one's inner spirit to achieve a particular desire. However, the method and implementation is not as simple as we describe it especially when faced with staff serving on a contract or part-time basis. These people are not actually bound to or at any time can leave the organization if there is a more secure opportunity in their lives in the future. In this regard, the Smallholder Development Research Division (SDRD) is also not exempted from the phenomenon of employee interchanges in which more than 81 percent of its 740 staff are contracted. Therefore, based on this phenomenon, the researchers decided to conduct a study on the impact and implications of retention of contract workers among civil servants at a statutory body agency in Bangi, Malaysia. The objective of this study was to explore the impulses or desires and strategies of the organization that affect employee retention among contract staff at SDRD. Thus, to achieve this objective, a study was established: What is the impulse or desire that affects the retention of employees among contract staff at SDRD? The study went through a qualitative approach using a semi-structural interview method. The data and information were collected through in-depth interview sessions, participating observations and analysis of study-related documents. The next process was analysing the data where the data obtained were given codes, categories and sub-themes to form the main theme in answering all the study questions. A total of 3 themes were formed to answer the main questions of this study, namely a conducive working environment and positive colleagues, more secure employment opportunities in SDRD and the equality of contract and permanent workers. Maslow's Hierarchy of Needs Theory of five levels of needs are closely related to Herzberg's Two-Factor Theory of intrinsic rewards and extrinsic rewards. In turn, these two theories influence employee retention among contract staff in SDRD.